Efficacy and Side Effects of Deferasirox and Deferiprone for Thalasemia Major in Children - Rindarwati, Asti Y.; Diantini, Ajeng; Lestari, Keri (Universitas Padjadjaran, Indonesia)
Thalassemia major (TM) is an inherited disease caused by defective or absent of hemoglobin chain synthesis. Regular chelation therapy is necessary to reduce excess iron in several organs of TM patients. The most commonly used chelating agents are deferasirox and deferiprone. However, information regarding their effectiveness and side effects in Indonesian children population with TM were limited. This study was conducted to assess the effectiveness and side effects of deferasirox and deferiprone in pediatric patients with TM. This was an observational study with prospective analysis which was conducted during April-August 2015. We included pediatric patients with TM who visited a hospital in Bandung, Indonesia, using consecutive sampling method. Thirty two subjects were divided into two groups, i.e., deferasirox and deferiprone group. Review of medical records and interview were performed for each participants. Effectiveness was defined as reduction in ferritin level. Side effects were assessed using Naranjo scale. Data were analyzed using Mann-Whitney test, Wiloxon test and Chi square test. P value < 0.05 defined statistical significance. We found that deferasirox was more effective than deferiprone for the treatment of TM in pediatric patiens, with less side effects. The use of deferasirox as iron chelating agent is recommended for patients with TM.Keywords: deferasirox, deferiprone, ferritin, thalassemia major